TINJAUAN YURIDIS TERHADAP KETIADAAN LABEL PERINGATAN BAHAYA PADA ROKOK ELEKTRIK BERDASARKAN UU PERLINDUNGAN KONSUMEN - Husein S, M. Syarif; Zulham, Zulham (UNES Law Review, 2023)
This study uses a normative juridical research type that refers to law or legislation and other literature as literacy support. The research approach used is in the form of statutory and conceptual approaches to answer the problems being researched with primary legal sources in this study in the form of laws Law Number 8 of 1999 concerning Consumer Protection. The results of this study explain that there is a neglect of the theory of legal certainty in regulating health information on electronic cigarettes in Indonesia. This is because the regulation of electronic cigarettes until now is only contained in the Minister of Finance Regulation No.146/PMK.010/2017 concerning customs and excise rates only and is not accompanied by legality related to electronic cigarette health information, of course this regulatory vacuum is very contrary to guarantees on consumer rights contained in article 4 of Law no. 8 of 1999 namely the right to correct, clear and honest information about a product/goods. So it is very dangerous if consumers are essentially Indonesian people consuming goods whose health standards are unclear.